2019
DOI: 10.1177/1524838018821956
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilities Relevant for Commercial Sexual Exploitation of Children/Domestic Minor Sex Trafficking: A Systematic Review of Risk Factors

Abstract: The commercial sexual exploitation of children (CSEC) and domestic minor sex trafficking (DMST) occur across the United States, violating the rights and health of far too many children and youth. Adequate prevention efforts should seek to understand the factors that make minors vulnerable to sexual exploitation in order to properly design programs to prevent victimization. This review presents the identified risk factors collected via a systematic literature review. Following full-text review, 15 studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(94 citation statements)
references
References 38 publications
6
82
0
6
Order By: Relevance
“…These results coincide with other studies about trafficked individuals and minors trapped in brothels [9,42]. Studies in other countries have found that youth who trade sex are especially vulnerable to HIV and related risks, including violence, less access to assistance, and higher chances of others controlling their sex-trade involvement [7,43,44]. In a Baltic Sea Regional Study on Adolescents’ Sexuality [22], 20–36% of Russian adolescent girls aged 16–18 reported having experienced any kind of non-penetrative sexual offenses, and 6–13% reported having experienced sexual abuse in the form of sexual intercourse.…”
Section: Discussionsupporting
confidence: 89%
“…These results coincide with other studies about trafficked individuals and minors trapped in brothels [9,42]. Studies in other countries have found that youth who trade sex are especially vulnerable to HIV and related risks, including violence, less access to assistance, and higher chances of others controlling their sex-trade involvement [7,43,44]. In a Baltic Sea Regional Study on Adolescents’ Sexuality [22], 20–36% of Russian adolescent girls aged 16–18 reported having experienced any kind of non-penetrative sexual offenses, and 6–13% reported having experienced sexual abuse in the form of sexual intercourse.…”
Section: Discussionsupporting
confidence: 89%
“…Childhood maltreatment trauma posed the strongest risk factor for CSEC, supported by the majority of studies (e.g., see Chohaney, 2016; Franchino-Olsen, 2019; Havlicek et al, 2016; O’Brien et al, 2017; Reid, 2014; Reid et al, 2015), thus corroborating findings of an earlier systematic review by Choi (2015) and a meta-analysis by De Vries and Goggin (2018). School nurses, as trusted health professionals in the school setting, are uniquely positioned to identify the signs and symptoms of child maltreatment trauma, as child victims of CSA or other forms of abuse are likely to see their school nurse for related physical and psychological health complaints.…”
Section: Discussionmentioning
confidence: 78%
“…As summarized in Table 2, there are numerous risk factors noted in peer-reviewed studies that increase a minor’s vulnerability to exploitation. As discussed a previous review (Franchino-Olsen, 2019), some key points regarding these risk factors include that, according to published research, many exploited minors have a prior history of child abuse, neglect, and/or maltreatment, which potentially heightens their vulnerability to CSEC/DMST (Cobbina & Oselin, 2011; Cole & Sprang, 2015; Fedina, Williamson, & Perdue, 2016; Havlicek, Huston, Boughton, & Zhang, 2016; Kaestle, 2012; Landers, McGrath, Johnson, Armstrong, & Dollard, 2017; Reid, 2011; Reid, Baglivio, Piquero, Greenwald, & Epps, 2017; Roe-Sepowitz, 2012). Childhood sexual abuse is frequently singled out a particularly salient risk factor among the categories of abuse as it can damage a child’s coping skills, damage their trust of and relationship with caregivers, and possibly motivate criminal, risky, or harm-seeking behaviors during adolescence (Chohaney, 2016; Kaestle, 2012; Martin, Hearst, & Widome, 2010; O’Brien, White, & Rizo, 2017; Reid & Piquero, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a negative home environment brought about by factors such as compromised parenting, caregiver strain, or witnessing family violence is associated with exploitation, as is the influence of their social network via peer or family member involvement in trading sex (Chohaney, 2016; Cobbina & Oselin, 2011; Cole & Sprang, 2015; Fedina et al, 2016; Landers et al, 2017; Reid, 2011; Reid et al, 2017; Reid & Piquero, 2014, 2016). These commonly cited risk factors, along with others, and their nuances are discussed further in Franchino-Olsen (2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation